2021
DOI: 10.3390/antibiotics10040459
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Healthcare-Associated Infections in Neonates with Severe Respiratory Failure and the Impacts of Inappropriate Initial Antibiotic Therap

Abstract: Background: Multidrug-resistant (MDR) pathogens have emerged as an important issue in neonatal intensive care units (NICUs), especially in critically ill neonates with severe respiratory failure. We aimed to investigate neonatal healthcare-associated infections (HAIs) caused by MDR pathogens and the impacts of inappropriate initial antibiotic therapy on the outcomes. Methods: We retrospectively analyzed all cases of HAIs in neonates with severe respiratory failure in a tertiary-level NICU in Taiwan between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…After the propensity score analysis, we found that ampicillin plus cefotaxime increased the risk of final adverse outcomes. The higher risk of final in-hospital mortality may be associated with the greater likelihood of MDR bacteremia, which has been documented to be associated with a higher risk of treatment failure and infectious complications [ 10 , 26 , 27 , 28 ]. The occurrence of MDR bacteremia and infectious complications will lead to a higher risk of recurrent sepsis and then a vicious circle will occur, which can explain the prolonged duration of hospitalization in neonates with initial broad-spectrum antibiotics [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the propensity score analysis, we found that ampicillin plus cefotaxime increased the risk of final adverse outcomes. The higher risk of final in-hospital mortality may be associated with the greater likelihood of MDR bacteremia, which has been documented to be associated with a higher risk of treatment failure and infectious complications [ 10 , 26 , 27 , 28 ]. The occurrence of MDR bacteremia and infectious complications will lead to a higher risk of recurrent sepsis and then a vicious circle will occur, which can explain the prolonged duration of hospitalization in neonates with initial broad-spectrum antibiotics [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have documented that the neonates with candidemia had a significantly higher rate of septic shock at the onset than late-onset sepsis caused by Gram-positive or even some Gram-negative pathogens [ 28 ]. Additionally, most of the neonates with candidemia had underlying chronic comorbidities, which has been documented to be the independent risk factor of the final adverse outcomes [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57] These studies assume that an appropriate antibiotic is ultimately administered within 1-3 days of symptom onset. 58 Unfortunately, P. thiaminolyticus can be difficult to recover using culture and will be consistently missed in Uganda and other parts of the world where neonatal sepsis is common. 59,60 Thus, it is likely that many infected neonates do not receive effective antimicrobial therapy at all, thus increasing the risk of mortality and serious sequelae, including PIH.…”
Section: Discussionmentioning
confidence: 99%